PENGARUH LOCUS OF CONTROL, FINANCIAL KNOWLEDGE, INCOME TERHADAP FINANCIAL MANAGEMENT BEHAVIOR - IDA IDA; CINTHIA YOHANA DWINTA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2010)
The aim of this study is to test impact locus of control, financial knowledge and income to financial management behavior. Total respondents are 130 respondents. Using regression analysis, the result shows financial knowledge impact financial management behavior but locus of control and personal income don’t impact financial management behavior. Because the sample of this research is student and almost of them have income from their parents.